Telecommunication techniques and systems (IV): all-optical timing techniques in ultra-high speed optical time-division-multiplexed system - Law, Choi Look (2008)
This project focuses on timing performance analysis for both the two circuits and great efforts are contributed to the development of the analytical models for calculating the root mean square (RMS) phase jetter and rms amplitude jitter of the extracted optical clock for both the two clock extraction circuit.